2018
DOI: 10.3389/fmicb.2018.00985
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Antiretroviral Restriction Factor Profiling Reveals the Evolutionary Imprint of the ex Vivo and in Vivo IFN-β Response in HTLV-1-Associated Neuroinflammation

Abstract: HTLV-1-Associated Myelopathy (HAM/TSP) is a progressive neuroinflammatory disorder for which no disease-modifying treatment exists. Modest clinical benefit from type I interferons (IFN-α/β) in HAM/TSP contrasts with its recently identified IFN-inducible gene signature. In addition, IFN-α treatment in vivo decreases proviral load and immune activation in HAM/TSP, whereas IFN-β therapy decreases tax mRNA and lymphoproliferation. We hypothesize this “IFN paradox” in HAM/TSP might be explained by both cell type- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
3
12
0
Order By: Relevance
“…Other members of the TRIM family, such as TRIM19/PML, were found to be negatively correlated with HTLV-1 Tax mRNA expression levels [17]. In line with previous work showing that TRIM19/PML interferes with HTLV-1 replication via Tax proteosomal degradation in ATL patients [18], all these data reinforce the potential involvement of the TRIM family in the early restriction of HTLV-1 replication.…”
Section: Htlv-1 Infection Cycle and Host Restriction Factors (Figure 1)supporting
confidence: 82%
See 1 more Smart Citation
“…Other members of the TRIM family, such as TRIM19/PML, were found to be negatively correlated with HTLV-1 Tax mRNA expression levels [17]. In line with previous work showing that TRIM19/PML interferes with HTLV-1 replication via Tax proteosomal degradation in ATL patients [18], all these data reinforce the potential involvement of the TRIM family in the early restriction of HTLV-1 replication.…”
Section: Htlv-1 Infection Cycle and Host Restriction Factors (Figure 1)supporting
confidence: 82%
“…In a cohort of 60 ATL patients, in whom the authors observed loss-of-expression mutations in several viral genes, including Tax, the HBZ oncogene remained intact [27]. Consistently, Leal et al [17] pointed to a large "antiviral cluster", a negative correlation between different members of the APOBEC3 family and Tax mRNA levels, as having greater impact than PVLs, clinical status or HAM/TSP parameters. Interestingly, an increase in h3AB, but not h3AG, was recently reported in HTLV-1-infected humanized mice exhibiting ATL-like features [28], a finding in line with that of another integrated molecular analysis showing increased h3AB expression in large ATL and AC cohorts [29].…”
Section: Apobec Familymentioning
confidence: 72%
“…HDACi used alone can be used to induce expression of BLV and HTLV-1 and reduce proviral loads [ 37 , 38 , 78 ]. However, the effect is only transient in HAM/TSP patients [ 40 ], and may be related to temporal fluctuations in viral RNA and response to immune control mechanisms in these patients [ 250 , 251 , 252 ]. Improved therapies include VPA combinations with zidovudine (AZT) or cytokines (IFNα) [ 253 , 254 , 255 ].…”
Section: Discussionmentioning
confidence: 99%
“…- [13] Negative correlation between members of APOBEC3 family and Tax mRNA levels. + [14] In [28] No effect on HTLV-1 and Tax expression in macrophages and cycling CD4+ T cells.…”
Section: Trim Familymentioning
confidence: 99%
“…Regarding TRIM Family implication, all data reinforce the potential involvement of the TRIM family in the early restriction of HTLV-1 replication. The majority of the data are obtained by whole exome sequencing analysis [13] or microarray analysis of CD4+ T Cells [14] in HAM/TSP cohorts of patients. Consistently with the fact that HTLV-1 mainly replicates by clonal expansion and the fact that virions are poorly infective, the involvement of APOBEC family, as well as BST2/Tetherin, remains uncertain.…”
Section: Introductionmentioning
confidence: 99%